DISTRIBUSI SPASIAL KASUS DAN TEMPAT PERKEMBANGBIAKAN NYAMUK DEMAM BERDARAH DENGUE DI WILAYAH KERJA PUSKESMAS BANJARMANGU 1 TAHUN 2025 - Dwi Atin Faidah; Setiya Aisyawa Galuh Megandalu; Bayu Suseno (Jurnal Ilmiah Medsains, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major public health concern in Indonesia, with a high number of reported cases. In 2024, there were 210,644 DHF cases with 1,239 deaths. Central Java Province contributed 12,994 cases, while Banjarnegara Regency reported 889 cases with an incidence rate (IR) of 83.8 per 100,000 population. The high number of cases in the working area of Banjarmangu 1 Health Center, along with the suboptimal use of spatial approaches, forms the basis of this research. The aim of this study is to describe the spatial distribution of DHF cases and mosquito breeding sites, as well as the characteristics of patients and related environmental factors. This research is a descriptive observational study with a cross-sectional approach. The study was conducted in the working area of UPTD Puskesmas Banjarmangu 1, Banjarnegara Regency, in May-June 2025. Data were obtained through observations and secondary data from the health center, the Meteorology, Climatology, and Geophysical Agency (BMKG), and other related institutions. Spatial analysis was conducted using ArcGIS 10.8.2 software and presented in thematic maps and descriptive tables.The results showed that adults were the most affected age group (73.7%), with a higher proportion of female patients (63.2%), and the most common education levels were elementary and senior high school. The highest number of cases was found in Jenggawur Village. Furthermore, a total of 187 mosquito breeding sites were identified, 57 of which were found to be positive for larvae. The study produced spatial distribution maps of DHF cases and mosquito breeding site locations in the study area. These findings indicate that DHF transmission is closely related to environmental factors and the presence of breeding sites around residential areas. Spatial-based control strategies, integrated larval source management, and increased community education need to be optimized to reduce the risk of sustained DHF transmission.